PLA and PP Composite Nonwoven with Antimicrobial Activity for Filtration Applications - Marta Łatwińska; Jadwiga Sójka-Ledakowicz; Jerzy Chruściel; Maciej Piórkowski (International Journal of Polymer Science, 2016)
The PLA (50% wt.)/PP (50% wt.), PLA (47.5% wt.)/PP (47.5% wt.)/paraffin (5% wt.), and PLA (47.25% wt.)/PP (47.25% wt.)/paraffin (5% wt.)/CuO·SiO2 (0.5% wt.) composite nonwovens were obtained in one-step process by using the melt-blown technique. Thermal properties (by the DSC method), physicomechanical parameters, specific surface area, the structure (by the SEM method), the elemental analysis (by the EDS method), and susceptibility to hydrolytic degradation (in alkaline and neutral media) were studied for all the obtained nonwovens. The antimicrobial properties of the composite nonwovens were determined by using dynamic contact conditions method, with three kinds of microorganisms applied. The DSC analysis of nonwovens revealed that the mixing of PLA and PP caused the decrease in homogeneity of both polymers, as well as a considerable increase in the PLA crystallization enthalpy. The paraffin and CuO·SiO2 addition to PLA/PP nonwoven generally improved the filtration properties and downgraded tensile strength. Among all the tested composite nonwovens, the PLA/PP/paraffin/CuO·SiO2 was the most and the PLA/PP/paraffin was the least susceptible to hydrolytic degradation in both media used in the study. The PLA/PP/paraffin/CuO·SiO2 composite nonwoven revealed strong antibacterial activity and slight activity against the yeast.